2007
DOI: 10.3147/jsfp.42.225
|View full text |Cite
|
Sign up to set email alerts
|

Upper Temperature Limits for the Multiplication of Betanodaviruses

Abstract: -Among the four types of betanodaviruses, redspotted grouper nervous necrosis virus (RGNNV) has the highest optimum temperature (25-30∞C) for its multiplication. We tested 16 RGNNV isolates for their temperature sensitivity in cultured cells and demonstrated that their upper temperature limits ranged from less than 30∞C to 35∞C. At the temperatures over the upper limits, viral RNA replication was inhibited similarly. These results indicate that temperatures mainly affect RNA replication or earlier virus multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…The optimum temperature for virus multiplication ranges from 15 °C to 30 °C depending on NNV genotypes and upper limit temperatures range from 32 °C to 35 °C. It has been reported that these temperatures mainly depend on genomic RNA1 which encodes RNA polymerase, although genomic RNA2 coding for CP also plays a role 3034 . Infectivity of NNV gradually declines at 37 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature for virus multiplication ranges from 15 °C to 30 °C depending on NNV genotypes and upper limit temperatures range from 32 °C to 35 °C. It has been reported that these temperatures mainly depend on genomic RNA1 which encodes RNA polymerase, although genomic RNA2 coding for CP also plays a role 3034 . Infectivity of NNV gradually declines at 37 °C.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also observed that optimal culture temperatures vary among genotypes: 15–20 °C for the BFNNV genotype, 20 °C for the TPNNV genotype, 20–25 °C for the SJNNV genotype and 25–30 °C for the RGNNV genotype [ 12 ]. More recent studies have highlighted that it is the RGNNV genotype that can replicate in vitro at the widest range of temperatures, from a minimum of 15 °C to a maximum of 35 °C [ 13 , 14 ]. Noteworthy, betanodaviruses are widely distributed worldwide in cold, temperate and tropical climate zones.…”
Section: Introductionmentioning
confidence: 99%
“…RGNNV has been isolated from diseased warm-water fishes, while BFNNV has been isolated from diseased cold-water fishes (Nishizawa et al, 1997;Aspehaug et al, 1999;Iwamoto et al, 1999;Thiery et al, 1999;Skliris et al, 2001;Johnson et al, 2002;Chi et al, 2003), suggesting that water temperature is an important factor influencing disease outbreaks. This is partly supported by in vitro virus proliferation studies showing the optimum growth temperature of the virus in cultured cells (Iwamoto et al, 2000;Lai et al, 2001;Ciulli et al, 2006;Hata et al, 2007). No difference was noticed in mortality caused by SJNNV infection in striped jack larvae reared in water of 20-26°C, while water temperature of 16-28°C influenced development of RGNNV disease in redspotted grouper.…”
mentioning
confidence: 81%